THE CORRELATION BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION OF THE SEVENTH GRADE STUDENTS OF SMPN 2 KELAYANG IN DESCRIPTIVE TEXT - Sentia, Diah; Erni, Erni; Azhar, Fadly (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The objective of this research was to examine the correlation betweenvocabulary mastery and reading comprehension of the seventh grade students ofSMPN2 Kelayang. A correlational designed was used in this research. The sample ofthis research is 27 students, it is class 7Cselected through using cluster randomsampling and recommended by English teacher. The instruments in this research weretwo kinds of test, they were vocabulary test and reading test, each test consisted of 30 multiple choice. All the data gained in this research was analyzed by using theformulation of Pearson Product Moment Correlation Coefficient. According to theresult of the analysis and statistical calculate, Based on correlation calculation it wasobtained that the correlation coefficient was 0.553 with a significance of 0.003. The (r-observed) df = n-2 (27-2 = 25) was 0.323 in the significant level 0.05. There showedthat the value of r-observed was higher than r-table (0.553>0.323) at the level medium correlation. Further, based on the computation coefficient determination, the R square obtained was 0.3058 or 30.58%. It means the relation existing between vocabulary mastery (X) and reading comprehension (Y) as much as 30.58%. In addition, normality test and linearity test also showed that both of the variables were normal and linear since sig. deviation linearity from the output SPSS 23.0 program was higher than the significant 0.05 (0.025>0.05) and the linearity greater than 0.05 (0.467>0.05). It can conclude that there was a significant and positive the correlation between vocabulary mastery and reading comprehension of the seventh grade students of SMPN 2 Kelayang in descriptive text. Consequently, it was indicated that vocabulary mastery helps te students to comprehend the text in which students should have sufficient vocabulary that can help them in reading test.Key Words: Correlation, Vocabulary Mastery, Reading Comprehension, Descriptive text